Clinical Forensic Medicine in Medical Education: Assessing The Current and Future Needs (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Clinical forensic medicine bridges the gap between medicine and law, focusing on the application of medical knowledge to legal issues. Though not a separate entity theoretical Clinical Forensic Medicine is already incorporated into existing undergraduate MBBS curriculum for third year students. This study aimed to assess the need for Clinical Forensic Medicine (CFM) training for undergraduate medical students of 3rd, 4th and 5th year.Materials and methods: A descriptive cross-sectional study was conducted among 300 medical students who answered a survey on Clinical Forensic Medicine in Medical Education in Chattogram Maa O Shishu Hospital Medical College. The questionnaire assessed participants' perceptions on medical and legal issues encountered in clinical practice and their views on the necessity of CFM training in their undergraduate medical curriculum under BMDC.   Results: 90.7% students accepted that their medical curriculum must inculcate CFM training in their curriculum. 40.33% students reported having inadequate time to complete their curriculum. 47.67% students acknowledged that practical classes could be an effective method for training in CFM. 53.4% felt that learning CFM in the third year was too early for them.64.7% of students felt that hands on training in CFM should be included in their undergraduate medical curriculum.  Conclusion: Theoretical knowledge with practical and bedside training can broaden students understanding of CFM.JCMCTA 2024 ; 35 (2) : 22-27